Jejunogastric intussusception - Hasan, Mahmud; Mahamud, MM; Khan, SA; Rahaman, M (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):255-9. The abstract of this article is available on the PubMed website